ANALISIS HUKUM TATA RUANG TERHADAP PROBLEMATIKA PERLINDUNGAN TANAH ADAT DI BALI DALAM DINAMIKA INVESTASI PARIWISATA - Widiartana, Putu Wahyu; Zulkarnain, I Gusti Agung Kiddy Krsna (VYAVAHARA DUTA, 2025)
Bali is widely recognized as a world-class tourism destination that relies on its rich natural resources, cultural heritage, and living customary values embedded within its communities. Behind the rapid development of the tourism sector lies serious pressure on the sustainability of customary land, which has long served as the foundation of the cultural and spiritual identity of Bali's traditional village communities. The conversion of customary land into tourism areas has created tensions between economic interests and the sacred values embedded in communal land rights systems. This study aims to analyze the extent to which spatial planning law in Bali provides protection for customary land and to examine the potential for harmonization between spatial planning regulations and prevailing customary legal norms. This research employs a normative legal method, using both statutory and conceptual approaches. The findings indicate that although customary land is normatively recognized in regional regulations and spatial planning policies, its implementation remains limited due to minimal involvement of traditional villages, the dominance of positivist legal paradigms, and a sectoral orientation prioritizing economic interests. Traditional villages and awig-awig as sources of local law have not been fully integrated into the spatial planning process. There is a need for legal policies that embrace the principles of legal pluralism and spatial justice by fostering stronger participatory mechanisms for indigenous communities in shaping development directions and managing their living spaces.